Artificial Intelligence and the Transformation of Learning Practices in Arabic Language Education: Student Perceptions, Benefits, Risks, and Ethical Challenges: Artificial Intelligence dan Perubahan Praktik Belajar dalam Pembelajaran Bahasa Arab: Persepsi Mahasiswa, Manfaat, Risiko, dan Tantangan Etis - Taftinatul ilmiyah; Sri Wahyuni; M. Khairil Ammar (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2026)
Artificial Intelligence (AI) is increasingly integrated into language learning in higher education and has the potential to transform students’ learning practices. Although previous studies have highlighted the effectiveness of AI in Arabic language learning, empirical research examining students’ responses, perceived benefits, and challenges in its use remains limited. This study aims to analyze students’ responses to AI, identify its benefits, and examine the challenges encountered in Arabic language learning. Using a descriptive qualitative approach, this study involved eight fifth- to seventh-semester students of the Arabic Language and Literature Program at Kiai Haji Achmad Siddiq State Islamic University of Jember selected through purposive sampling. Data were collected through structured interviews and non-participant observation and analyzed using the Miles and Huberman interactive model. The findings indicate that students generally respond positively to AI because it facilitates text comprehension, supports the understanding of nahwu-shorrof rules, enriches vocabulary, and improves learning efficiency. However, this acceptance is accompanied by concerns regarding dependency, accuracy limitations, and shifts toward more instant learning strategies. These findings underscore the importance of integrating AI proportionally to support Arabic language learning while maintaining students’ academic autonomy and learning quality.